2021
DOI: 10.1038/s41467-021-25409-6
|View full text |Cite
|
Sign up to set email alerts
|

Computational models of category-selective brain regions enable high-throughput tests of selectivity

Abstract: Cortical regions apparently selective to faces, places, and bodies have provided important evidence for domain-specific theories of human cognition, development, and evolution. But claims of category selectivity are not quantitatively precise and remain vulnerable to empirical refutation. Here we develop artificial neural network-based encoding models that accurately predict the response to novel images in the fusiform face area, parahippocampal place area, and extrastriate body area, outperforming descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 69 publications
(71 reference statements)
4
83
0
Order By: Relevance
“…We used convolutional neural networks (CNNs) and fMRI data to create image-computable voxelwise encoding models of mid-level feature tuning in the PPA. CNNs are theoretical models of the core information-processing mechanisms implemented by biological neural populations, and they are the leading computational models of human visual cortex 28 , including scene-selective areas 24, 25, 29 . They perform a set of biologically plausible mathematical operations, and their hierarchical, convolutional architecture is inspired by the primate visual system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used convolutional neural networks (CNNs) and fMRI data to create image-computable voxelwise encoding models of mid-level feature tuning in the PPA. CNNs are theoretical models of the core information-processing mechanisms implemented by biological neural populations, and they are the leading computational models of human visual cortex 28 , including scene-selective areas 24, 25, 29 . They perform a set of biologically plausible mathematical operations, and their hierarchical, convolutional architecture is inspired by the primate visual system.…”
Section: Resultsmentioning
confidence: 99%
“…Another key finding showed that the category-selective organization of object representations in the macaque ventral stream can be mapped onto the first two principal components of a feedforward CNN and may thus naturally arise from the statistical structure of visual feature representations 36 . It has also recently been shown the feedforward neural network models provide more accurate predictions of response preferences in category-selective visual regions than descriptive models of image categories or the predictions of experts in the field 25 . More broadly, multiple studies have found that the representations of the human ventral stream are better explained by perceptual features than by the abstract properties that underlie category identity or human intuitions about semantic similarity 25, 29, 43–45 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, some researchers are trying to build accurate models of the brain activity that, in essence, enable simulations of neuroscience experiments (e.g., Khosla & Wehbe, 2021;Ratan Murty et al, 2021). This type of modeling is especially important in cases when experimental data are expensive or hard to obtain: with a high-accuracy model of brain responses, a researcher can run thousands of experiments in silico, refine their hypothesis, and then test the final prediction in vivo.…”
Section: Build Accurate Models Of Brain Datamentioning
confidence: 99%
“…However, nameability of features may be an overly restrictive metric as it limits our understanding to a vocabulary that is heavily biased by a priori hypotheses and may not include words for the concepts we actually need (Buzsáki, 2019). For instance, recent work has shown that (a) neurons typically described as "face-responsive" respond more strongly to artificial images produced by DNNs than to natural images described by the word "face" (Ponce et al, 2019) and (b) a neural-network-based linearized model of activity in the fusiform face area predicts responses to faces better than label-based models (Ratan Murty et al, 2021), suggesting that simple verbal features cannot provide a full account of neural activity. To overcome the limitation of using individual nameable features, many researchers have instead started to use high-dimensional feature sets.…”
Section: Examine Individual Featuresmentioning
confidence: 99%